Causes of Inequality in Health : Who Are You? Where You Live? Or Who Your Parents Were? - Wagstaff, Adam; Paci, Pierella; Joshi, Heather (World Bank, Washington, DC, 2014)
Data from the British National Child Development Study show that, among 33-year-olds, ill health (as measured by cardinalized responses to a question on self-assessed health) is concentrated among the worse off. The authors seek to decompose the inequalities in health status into their socioeconomic causes. In this decomposition, inequalities in health status depend on inequalities in each of the underlying determinants of health and on the elasticities of health status with respect to each of these determinants. The authors estimate these elasticities using regression models that allow for unobserved heterogeneity at the community level. They find that inequalities in unobserved community-level influences account for only 6 percent of health inequality, and inequalities in parental education and social class for only 4 percent. Inequalities in income and housing tenure account for most health inequality, though inequalities in educational attainment and in math scores at age seven also play a part.